Histopathological Evaluation of Angiogenic Markers in Non-Hodgkin's Lymphoma - Singh, Priyanka; Tahlan, Anita; Mohan, Harsh; Singh, Ram (Journal of Laboratory Physicians, 2023)
Background Angiogenesis plays a key role in the development, maintenance, and progression of tumor. The incidence of non-Hodgkin's lymphoma (NHL) is increasing from the past three decades.Materials and Methods The aim of the study is to evaluate microvessel density (MVD) using CD34 monoclonal antibody and vascular endothelial growth factor (VEGF) using monoclonal antibody that were studied in pretreatment paraffin-embedded tissue samples of 60 cases.Results MVD was found to be increased in parallel with increasing grade of tumor. B-NHL had a mean MVD of 79.5 ± 8.8 (no./mm2), while T-NHL had a mean MVD of 183 ± 37.6 (no./mm2). VEGF expression was seen in 42 cases (70%), 20 cases (33.3%) showed strong VEGF expression, and the remainder showed either weak (36.6%) or no (30%) staining. Strong VEGF expression is seen in 100% cases of T-NHL and 77.7% cases of B-NHL. Mean MVD and VEGF expression was found to be correlated significantly with the histological grade of NHL (p = 0.001 and p = 0.000, respectively). Average microvessel counts were 53, 82.9, and 130.8 vessels (no./mm2) for negative, weak, and strong VEGF staining, respectively. These differences were statistically significant (p = 0.005 for strong vs. negative and p = 0.091 for strong vs. weak VEGF staining individually).Conclusion As the grade of tumor progresses, the angiogenic potential also advances which seems to depend on VEGF. The presence of higher MVD in high-grade lymphomas can be utilized for antiangiogenic drugs.
Keywords: angiogenesis; CD34; hot spots; microvessel density; non-Hodgkin's lymphoma